ANALISIS KESALAHAN EJAAN PADA MAKALAH MAHASISWA SEMESTER 7 PRODI PBSI - Siti Aisyah Salsabila; Miftahul Huda (PENTAS : Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2024)
Spelling is the depiction of language sounds in writing, including the use of letters and punctuation marks. Meanwhile, error analysis is an investigation into something related to deviations that occur. Therefore, this research aims to identify spelling errors in writing papers by 7th semester students of the PBSI Study Program, Darul Ulum Lamongan Islamic University. This research uses qualitative methods. The data for this research are spelling errors in the form of use of capital letters, punctuation, italics, use of prepositions in the 7th semester student papers of the PBSI Study Program at Darul Ulum Lamongan Islamic University. Data collection techniques use listening, reading and note-taking techniques. Analysis of this research data means carefully reading the data in the form of spelling errors that have been obtained, then recording each spelling error and making conclusions. From the research results, 25 errors were obtained, including: 6 data errors in writing capital letters, 4 data errors in using italics, 9 data errors in using punctuation marks, and 6 data errors in using prepositions.